Ancylostoma caninum Anticoagulant Peptide Blocks Metastasis In Vivo and Inhibits Factor Xa Binding to Melanoma Cells In Vitro - Donnelly, Kathleen M.; Bromberg, Michael E.; Milstone, Aaron; McNiff, Jennifer Madison; Terwilliger, Gordon; Konigsberg, William H.; Cappello, Michael (Thrombosis and Haemostasis, 1998)
We evaluated the in vivo anti-metastatic activity of recombinant Ancylostoma caninum Anticoagulant Peptide (rAcAP), a potent (Ki = 265 pM) and specific active site inhibitor of human coagulation factor Xa originally isolated from bloodfeeding hookworms. Subcutaneous injection of SCID mice with rAcAP (0.01-0.2 mg/mouse) prior to tail vein injection of LOX human melanoma cells resulted in a dose dependent reduction in pulmonary metastases. In order to elucidate potential mechanisms of rAcAP’s anti-metastatic activity, experiments were carried out to identify specific interactions between factor Xa and LOX. Binding of biotinylated factor Xa to LOX monolayers was both specific and saturable (Kd = 15 nM). Competition experiments using antibodies to previously identified factor Xa binding proteins, including factor V/Va, effector cell protease receptor-1, and tissue factor pathway inhibitor failed to implicate any of these molecules as significant binding sites for Factor Xa. Functional prothrombinase activity was also supported by LOX, with a half maximal rate of thrombin generation detected at a factor Xa concentration of 2.4 nM. Additional competition experiments using an excess of either rAcAP or active site blocked factor Xa (EGR-Xa) revealed that most of the total factor Xa binding to LOX is mediated via interaction with the enzyme’s active site, predicting that the vast majority of cell-associated factor Xa does not participate directly in thrombin generation. In addition to establishing two distinct mechanisms of factor Xa binding to melanoma, these data raise the possibility that rAcAP’s antimetastatic effect in vivo might involve novel non-coagulant pathways, perhaps via inhibition of active-site mediated interactions between factor Xa and tumor cells.